Action research and commoning: positioning architectural research in (or with) local grassroot group (EAAE Annual Conference Proceedings, 2023)
The proposed contribution is based on two case studies where architect-researchers and local actors partner as collaborators in commoning efforts. The first case develops around an ‘urban common’ (as named by the local council) Moruzzi Road in Pavia, Italy. The second one involves reappropiation of a disused open space as a community orchard at Huddersfield, UK.